Disrespect and abuse of women during childbirth in Nigeria: A systematic review. - Foluso Ishola; Onikepe Owolabi; Veronique Filippi (PLoS ONE)
Background Promoting respectful care at childbirth is important to improve quality of care and encourage women to utilize skilled delivery services. However, there has been a relative lack of public health research on this topic in Nigeria. A systematic review was conducted to synthesize current evidence on disrespect and abuse of women during childbirth in Nigeria in order to understand its nature and extent, contributing factors and consequences, and propose solutions. Methods Five electronic databases were searched for relevant published studies, and five data sources for additional grey literature. A qualitative synthesis was conducted using the Bowser and Hill landscape analytical framework on disrespect and abuse of women during childbirth. Results Fourteen studies were included in this review. Of these studies, eleven were cross sectional studies, one was a qualitative study and two used a mixed method approach. The type of abuse most frequently reported was non-dignified care in form of negative, poor and unfriendly provider attitude and the least frequent were physical abuse and detention in facilities. These behaviors were influenced by low socioeconomic status, lack of education and empowerment of women, poor provider training and supervision, weak health systems, lack of accountability and legal redress mechanisms. Overall, disrespectful and abusive behavior undermined the utilization of health facilities for delivery and created psychological distance between women and health providers. Conclusion This systematic review documented a broad range of disrespectful and abusive behavior experienced by women during childbirth in Nigeria, their contributing factors and consequences. The nature of the factors influencing disrespectful and abusive behavior suggests that educating women on their rights, strengthening health systems to respond to specific needs of women at childbirth, improving providers training to encompass interpersonal aspects of care, and implementing and enforcing policies on respectful maternity care are important. This review has also shown that more robust research is needed to explore disrespect and abuse of women during childbirth in Nigeria and propose compelling interventions.